A Preliminary Research Design and Model Determinants of Ship Accident Risk in Indonesia: The Roles of Competence, Work Stress, Communication, and Supervision through Safety Culture - Danny Faturachman; Edi Abdurachman (International Journal of Marine Engineering Innovation and Research, 2026)
Indonesia is the world’s largest archipelagic state, where sea transport is the backbone of passenger and cargo mobility, yet ship accidents remain frequent and often highly fatal. This paper proposes and tests a structural model linking four human-factor dimensions—crew competence, work stress, communication effectiveness, and supervision—to perceived ship accident risk in Indonesia, with safety culture as a mediating variable. A quantitative survey is conducted among 300 seafarers operating in three major maritime regions (Batam, Merak, and Bali), and data are analyzed using Structural Equation Modeling (SEM) following recommended rules of thumb for sample size and model evaluation. The study aims to identify the most influential human-factor determinants of perceived accident risk and to provide evidence-based recommendations for strengthening maritime safety culture.